Environmental Evaluation of Experimental Heat-treated Oriented Strand Board - Sugahara, Estefani S. [UNESP]; Dias, André Manuel Alves; Botelho, Edson Cocchieri [UNESP]; Dias, Alfredo Manuel Pereira Geraldes; de Campos, Cristiane Inácio [UNESP] (My University, 2024)
The use of wood-based panels such as Oriented Strand Board has grown in civil construction. This follows the contemporary trend towards low environmental impact materials. However, there is a lack of relevant information about their life cycle assessment, appearing as a current and relevant research topic. Experimental panels made with Eucalyptus wood and castor oil-based polyurethane adhesive already demonstrated great physical-mechanical performance. Therefore, this study aimed to continue the evaluation of this innovative product, estimating their potential environmental impacts using life cycle assessment from a cradle-to-gate perspective and comparing the results with traditional panels and literature data. System boundaries, environmental impacts and environmental hotspots were identified using the ReCiPe H method in terms of ten impact categories. Comparing experimental (heat-treated) and traditional panels, the experimental versions performed better in most categories and showed safer behavior in categories related to human health in addition to not using paraffin, termiticide, and other organic chemicals presented in the traditional panels. Though made of different types of adhesives, the adhesive was the main environmental hotspot for both types.
Keywords: Construction industry; Environmental impacts; LCA; Life cycle assessment; OSB